Ionic Liquid/Silica Sulfuric Acid Promoted Fast Synthesis of a Biginelli-Like Scaffold Reaction - Shaabani, Ahmad; Sarvary, Afshin; Rahmati, Abbas; Rezayan, Ali Hossein (Letters in Organic Chemistry, 2007)
Biginelli-like scaffolds were synthesized in good yields by a three-component condensation reaction of 5,5-dimethyl-1,3-cyclohexanedione, an aldehyde and urea, N-methylurea or thiourea in 1-butyl-3- methylimidazolium bromide ([bmim]Br) as ionic liquid (IL) in the presence of silica sulfuric acid (SSA) as solid acid catalyst at 100 °C within less than 2 hours.
Keywords: silica sulfuric acid